Case study analysis of green building certifications - Ober, Marissa (Kansas State University, 2024)
This report intends to provide a detailed comparison of two major green building certifications: Leadership in Energy and Environmental Design (LEED) and Living Building Challenge (LBC). The study examines the specific requirements, criteria, and standards of each certification, focusing on their approaches to promoting environmentally responsible construction. The report outlines the distinct features of both LEED and LBC, analyzing their strengths and weaknesses. It emphasizes the stringent nature of the LBC certification compared to LEED, particularly in reducing the environmental impact of the built environment. This report includes a focused case study on the Kendeda Building, a project that holds the dual distinction of being certified under both the LBC 3.0 and achieving LEED Platinum certification. The analysis of this building shows the criteria of the LBC, and the established standards of LEED can coexist within a single project. This report explores how both certifications align with the sustainability goals of reducing environmental impact, through the analysis of a building that has achieved both LBC 3.0 and LEED Platinum standards. This case study contributes to the understanding of the strengths and challenges associated with the application of these two prominent green building certifications. The report concludes that the Living Building Challenge is a more rigorous and impactful building certification than Leadership in Energy and Environmental Design, highlighting the importance of choosing certifications that significantly contribute to mitigating the built environment's impact on the natural environment.
Keywords: Green buildings; LEED; Living Building Challenge; The Kendeda Building